Mycobacteria Protocols - Parish, Tanya; Roberts, David M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
Updated and revised, this thorough volume provides a selection of the newest methods, as well as some of the basic methods required for a mycobacterial research laboratory.  Mycobacteria Protocols, Third Edition guides readers through fractionation and analysis of macromolecules, from nucleic acids to proteins, complex lipids, and metabolites.  Detailed and comprehensive protocols are provided for protein and lipid/glycolipid analysis using well-established methods; these are now complemented by a metabolomics chapter in which the complement of metabolites can be profiled. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.  Authoritative and up-to-date, Mycobacteria Protocols, Third Edition will be a resource both to those working in the field, and to newcomers.
Whole Genome Sequencing for Comparative Genomics and De Novo Genome Assembly -- Whole Transcriptome Sequencing for High-resolution Transcriptomic Analysis in Mycobacterium tuberculosis -- RNA Sequencing for Transcript 5’-end Mapping in Mycobacteria -- Fractionation and Analysis of Mycobacterial Proteins -- Lipid and Lipoarabinomannan Isolation and Characterization -- Metabolomics of Mycobacterium tuberculosis -- Electroporation of Mycobacteria -- Targeted Gene Knockout and Essentiality Testing by Homologous Recombination -- Construction of Conditional Knockdown Mutants in Mycobacteria -- Mycobacterial Recombineering -- In vitro Models that Utilize Hypoxia to Induce Non-replicating Persistence in Mycobacteria -- Genetic Dissection of Mycobacterial Biofilms -- Measuring Efflux and Permeability in Mycobacteria -- Single-cell Analysis of Mycobacteria using Microfluidics and Time-lapse Microscopy -- Antimicrobial Susceptibility Testing for Mycobacterium sp. -- Determination of Compound Kill Kinetics Against Mycobacterium tuberculosis -- Microplate Alamar Blue Assay (MABA) and Low Oxygen Recovery Assay (LORA) for Mycobacterium tuberculosis -- A Multi-Stress Model for High Throughput Screening Against Non-replicating Mycobacterium tuberculosis -- Isolation and Characterization of Compound-resistant Isolates of Mycobacterium tuberculosis -- Macrophage Infection Models for Mycobacterium tuberculosis -- Infection of Human Neutrophils to Study Virulence Properties of Mycobacterium tuberculosis -- Isolation of Bead-phagosomes to Study Virulence Function of M. tuberculosis Cell Wall Lipids -- Live Imaging of Mycobacterium marinum Infection in Dictyostelium discoideum -- Testing Chemical and Genetic Modulators in Mycobacterium tuberculosis Infected Cells using Phenotypic Assays.  .
Keywords: Microbiology; Microbiology